Transvaginal Photobiomodulation for the Treatment of Chronic Pelvic Pain: A Pilot Study - Ralph Zipper; Brian Pryor; Georgine Lamvu (Mary Ann Liebert, 2021)
Background: Chronic pelvic pain (CPP) is a common and debilitating condition that affects millions of U.S. women. Most treatments are ineffective and innovative new therapies are desperately needed. Large, controlled studies show that photobiomodulation (PBM) can reduce pain in patients with other chronic pain conditions, such as low back pain, neck pain, and fibromyalgia. The objective of this pilot study was to determine if transvaginal PBM (TV-PBM) can reduce pain in women with CPP. Methods: We conducted a before and after, observational, pilot study. Patients completed the Short Form-McGill Pain Questionnaire (SF-MPQ) at baseline, 1 week, 3 months, and 6 months after nine treatments of TV-PBM. Clinicians completed the Clinical Global Impression Scale (CGI) assessing patient illness severity at the same time. Wilcoxon rank-sum t-tests and effect size using Cohen's d coefficient (low effect size if d?<?0.2, medium if 0.2 < d?>?8, and high if d?>?0.8) was used to measure degree of pain improvement, which was also considered clinically significant if pain reduction was >30%. Results: Thirteen women completed 9 treatments, and 10 women were successfully followed to 6 months. At baseline, the mean SF-MPQ score was 19.7 (standard deviation [SD]???5.9). Compared with baseline, 60% improved; the mean SF-MPQ score decreased to 10.0 (SD ?7.5, p?=?0.004, d?=?1.6) at 1 week after treatment, to 9.7 (SD ?7.9, p?=?0.005, d?=?1.7) at 3 months, and 8.2 (SD ?8.1, p?=?0.002, d?=?1.9) at 6 months. Conclusion: Transvaginal PBM provided significant and sustained pain relief to women with CPP up to 6 months. Further controlled studies are needed to confirm these findings, however, in this initial pilot, TV-PBM shows promise.